Aplastic Anaemia, Acute Myeloblastic Leukaemia, and Oxymetholone - Delamore, I. W. (1971)
Four patients developed acute myeloblastic leukaemia after treatment of aplastic anaemia with oxymetholone. Two had previously shown an excellent clinical response to the drug and a third some improvement. Though no definite causal relationship between therapy and the onset of leukaemia has been established, the number of cases is greater than might have been expected by chance. The association of the two diseases is discussed.